LAGU BUKIT KEMENANGAN KARYA DJUHARI ARRANSEMEN MUSAFIR ISFANHARI - RATNA SARI, JULISTA (APRON Jurnal Pemikiran Seni Pertunjukan, 2016)
Abstract Music in Indonesia, era 50th-60th, be affected by situation of struggle for independence, so the songs is created in classical genre and revolution theme. So, Indonesian people called that classical song of seriosa. The 1980s Indonesia classical song of seriosa often used as a material competition at event Bintang Radio Televisi (BRTV) in solo singer classical seriosa category, and one of tittle’s song is Bukit Kemenangan composed by Djuhari. But, in 2000s Indonesia classical songs of seriosa didn’t popular again in general public, except in people who study in school of music. But, 2015 is new era, because of arranger from East Java called Musafir Isfanhari has been arrangement song of Bukit Kemenangan composed by Djuhari and than that song become material song in Pekan Seni Pelajar (PSP) 2015 Senior High School in East Java. So researches interest about arrangement of Musafir Isfanhari in song of Bukit Kemenangan composed by Djuhari This research make qualitative methods by observing Bukit Kemenangan composed by Djuhari, arranged by Musafir Isfanhari in the review arranging for voice, start from Vary the Texture, voice for effect and note-against-note vs call-and-respond. Data collection techniques based on observation which type roles as observer, and semi-structured interview the source to solve the problems, until documentation data and the result of interview. Based on miller’s book “The Complete Idiot’s Guide to Arranging and Orchestration”, the discussion technique of arranging for voice, arranged by Musafir Isfanhari on Bukit Kemenangan composed by Djuhari is used some techniques; (1) Vary the Texture which type vary the number of voice, vary the way voice are used, vary the voice spacing. (2) voice for effect which type for a shophisticated, to create a slightly unsetteled sound. (3) note-against-note vs call-and-respond. From all techniques that explained by the researcher, technique that most used by Musafir Isfanhari to arranging Bukit Kemenangan composed by Djuhari is vary the way voice are used to support the harmony of choir (sopran, alto, tenor, and bass), interval each voice need some variations in order not to cause boredom because of variety atmosphere. Key words: Song of Bukit Kemenangan, Arranging for Voice